PENGARUH LETAK, LUAS DAN BENTUK TERHADAP PEMERINTAHAN NEGARA SERTA BATAS NEGARA INDONESIA - Saragi, Nathasia Angelina; Kustiawan; Diah Ayu Sholeha; Desma Tri Anggriani; Omi (STISIP Widyapuri Mandiri, 2024)
This research aims to analyze the influence of location, area and form on state government based on the geographical context of Indonesian politics. The analysis was carried out by reviewing papers containing descriptions of the influence of the location, extent and shape of Indonesia in terms of political geography. The discussion begins with the influence of Indonesia's astronomical and geographical location, the size of its territory, islands and seas, as well as the shape of its landmass on state government. The research results show that geographical location, area and shape have positive and negative influences on Indonesian government in various political, economic, social and cultural aspects.